Instilling the Value of Cooperation in Dance Arts Learning for Deaf Students at SLB Negeri 1 Demak - Safitri, Yunita (Universitas Negeri Semarang, 2024)
Dance learning at SLB Negeri 1 Demak for deaf students uses learning materials determined by the teacher according to the student’s abilities. The dancers, children with special needs (ABK) or hearing impairments, are very different from normal children in general, such as in adjusting the tempo and the intensity of energy in dancing. Cooperation in dance learning is necessary to create a unified and beautiful dance. This research aims to analyze the cultivation of collaboration in dance learning for deaf students at SLB Negeri 1 Demak. This research used qualitative methods with data collection techniques, namely interviews, observation, and documentation. It used source triangulation and technical triangulation to validate data. In addition, data analysis includes data collection, data reduction, data presentation, and conclusions. The results show that dance learning for deaf students at SLB Negeri 1 Demak is conducted in three stages. The first stage is pre-learning activities by students and teachers through prayer and attendance. The second stage is core activities carried out by delivering learning materials using teaching materials and learning methods that support learning. The third stage is closing activities with questions and answers from students and teachers regarding the material and prayer. The cultivation of cooperation in dance learning was shown in the attitudes of students and teachers in collaboration, caring, and sharing.